CONCEPTUAL PRINCIPLES OF THE MECHANISM FOR ENSURING ECONOMICSECURITY OF ECONOMIC ENTITIES - PANCHENKO, Volodymyr; PANCHENKO, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article defines the necessity and consequences of ensuring economic security for business entities, which necessitates compliance with the basic principles of developing and implementing the appropriate mechanism. It is emphasized that the development and implementation of economic security mechanisms is the basic approach on the basis of which the management of business entities is able to organize all measures to ensure it. At the same time, the mechanism for ensuring the economic security of a business entity must take into account the entire set of prerequisites that can both hinder and stimulate an increase in the pace of its progress. The main elements of the mechanism for ensuring the economic security of a business entity are summarized, which include tasks (ensuring financial stability, reducing risks and threats, protecting assets and resources, increasing competitiveness, adapting to changes in the external environment, developing human resources, using information and communication technologies, complying with the norms and requirements of legal regulation), objects (financial stability, risk management, operational efficiency, information and analytical protection, personnel policy, legal security, adapting to changes in the external environment, innovative development), principles (systematicity, complexity, adaptability, continuity, economic feasibility, prevention, responsibility and control, legal responsibility, information security, partnership and interaction), tools (financial and economic, organizational and managerial, regulatory and legal, intellectual and personnel, information and analytical, technological and technical, marketing, investment and innovation, social and corporate, logistics). It is concluded that compliance with the basic provisions in the process of choosing and implementing an economic security mechanism will ensure not only a reduction in risks and threats, but also the creation of favorable conditions for the sustainable development of business entities in the long term.